Differentiation between normal and tumor mammary glands with depth-resolved attenuation coefficient from optical coherence tomography - Maciel, Marino Jesus Correia (2022)
Optical coherence tomography (OCT) is a well-established imaging technology for high-resolution, cross-sectional imaging of biological tissues. Imaging processing and light attenuation coefficient estimation allows to further improve the OCT diagnostic capability. In this paper we use a commercial OCT system, Telesto II-1325LR from Thorlabs, and demonstrate its ability to differentiate normal and tumor mammary mouse glands with the OCT attenuation coefficient. Using several OCT images of normal and tumor mammary mouse glands (n = 26), a statistical analysis was performed. The attenuation coefficient was calculated in depth, considering a slope of 0.5 mm. The normal glands present a median attenuation coefficient of 0.403 mm-1, comparatively to 0.561 mm-1obtained for tumor mammary glands. This translates in an attenuation coefficient approximately 39% higher for tumor mammary glands when compared to normal mammary glands. The OCT attenuation coefficient estimation eliminates the subjective analysis provided by direct visualization of the OCT images.